Polish-Ukrainian relations in the field of early music - Ignatenko, Yevgeniya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. Jubilee 2025 – for the harpsichord class, which celebrates the 30th anniversary, and the department of early music, which celebrates the 25th anniversary – encourages reflections, memories in order to restore and comprehend the events that were important. The harpsichord class is “older” than the department for five years. Its appearance and first successes inspired the then rector of the Ukrainian National Tchaikovsky Academy of Music, Oleh Tymoshenko, to open a department of early music, headed by the famous researcher of Ukrainian music, Nina Herasymova-Persydska. The proposed jubilee reflections are selective as they focus on PolishUkrainian relations, which had a significant impact on the life and progress of the jubilarians. The main objective of the study is to highlight the creative connections of the harpsichord class and the department of ancient music of the UNTAM with Polish musicians; to present the interaction of Polish and Ukrainian musicians within the framework of the international forum “Musica Antiqua Europae Orientalis” (Bydgoszcz, 1966–2006), the festivals “Ukraine and the Baroque World” (Kyiv, 1994), and “Bach’s Days” (Krakow, 2005, 2006), in the projects of the Bydgoszcz society “Heritage” (2013–2020). The study is based on the materials of interviews with musicians who developed Polish-Ukrainian relations in the field of early music (Nina Herasymova-Persydska, Svitlana Shabaltina, Elżbieta Stefańska). The methodology of the work is based on empirical and theoretical research methods (interviews, memories and observations, analysis and synthesis). Results and conclusions. The Polish-Ukrainian scientific projects and concerts, which were important for the development of the Kyiv cell of researchers and performers of early music, are highlighted and presented. The Polish press’ coverage of Ukrainian musicians’ performances is examined. Polish-Ukrainian musical connections in the field of early music influenced the post-Soviet restructuring of Ukrainian educational and cultural institutions. The long-term collaboration between Kyiv harpsichord player Svitlana Shabaltina and Polish harpsichord player Elżbieta Stefańska contributed to the development of the harpsichord class, which in 2000 became part of the Department of Early Music founded at the National Ukrainian Academy of Music. The Kyiv harpsichord class became the first professional cell of historically informed performance in Ukraine. During the time of Ukraine’s independence, many Ukrainian musicians have joined the European movement for the revival of early music and historically informed performance. The study of their experiences can provide a promising direction for future research.